Remedial program learning application / Nor Anis Sofia Mohd Hasazli - Mohd Hasazli, Nor Anis Sofia (2020)
Remedial program was created by Ministry of Education Malaysia that help remedial pupils who are struggle or slow learner in basic learning. Therefore, there were problems that faced by remedial pupils which were they have learning problem, unable to understand basic concept in Mathematic subject, and easy loss concentration and focus. Based on these issues, the aim of this research was to develop a Remedial Program Learning Application (RPLA) to help pupils in learning Mathematic session. A preliminary investigation (PI) was conducted at early stage to identify the existing materials teaching, learning styles of remedial program and finding suitable contents of Mathematic learning. The objectives of this research are to identify multimedia principle and Child Computer Interaction (CCI) principle in term of familiarity by design and develop a RPLA with Mathematic subject learning to evaluate interface design using Expert Review and Quasi Experiment for effectiveness of RPLA application. The methodology that applied was ADDIE Model. ADDIE Model consists of five phases which were Analysis, Design, Development, Implementation and Evaluation. The development of RPLA was constructed using Unity, Audacity and Adobe Photoshop. The learning application yields a positive impact to be effectiveness for remedial pupils in primary schools for Mathematic learning.